DIZEL YOQILG‘ILARI UCHUN 2-MERKAPTOBENZOKSAZOL EFIRLARINI PRISADKA SIFATIDA QO‘LLASH - Babaev , O; Fozilov , F (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
This article conducts scientific research in current areas, such as the creation of technological processes for the use of 2-mercaptobenzaxole esters as additives for diesel fuels.